2010
DOI: 10.11144/javeriana.upsy10-1.eaec
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de las actitudes de estudiantes de ciencias sociales y psicología: relevancia de la información y contacto con personas discapacitadas

Abstract: El objetivo de este artículo es conocer las actitudes hacia la discapacidad del alumnado procedente de titulaciones de Ciencias Sociales y Psicología, matriculado en asignaturas en las que se proporciona información sobre la discapacidad. También se pretende determinar la influencia en estas actitudes del contacto con discapacitados. Se aplicó la Escala de Actitudes Hacia las Personas con Discapacidad de Verdugo, Jenaro y Arias (1995) a un grupo de 470 estudiantes de la Universidad de Granada. Los resultados m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 14 publications
1
8
0
3
Order By: Relevance
“…What is noteworthy as well as worrying with respect to factor F2/PA5 is the existence of 17.7% of respondents who responded with levels four and five, stating that they agreed or totally agreed with schooling these students in special education centers, with some of these results being in line with those obtained by other researchers [ 11 , 16 , 53 ]. This fact reinforces the perception of the lack of training received on the rights recognized in the CRPD since it is quite contradictory that a majority of respondents (59.1%) are in favor of the educational inclusion of students with low functional performance in general education centers yet a high percentage also state that students with low functional performance should be schooled in special education centers (17.7%), surely a direct consequence of a lack of training on the convention.…”
Section: Discussionsupporting
confidence: 81%
“…What is noteworthy as well as worrying with respect to factor F2/PA5 is the existence of 17.7% of respondents who responded with levels four and five, stating that they agreed or totally agreed with schooling these students in special education centers, with some of these results being in line with those obtained by other researchers [ 11 , 16 , 53 ]. This fact reinforces the perception of the lack of training received on the rights recognized in the CRPD since it is quite contradictory that a majority of respondents (59.1%) are in favor of the educational inclusion of students with low functional performance in general education centers yet a high percentage also state that students with low functional performance should be schooled in special education centers (17.7%), surely a direct consequence of a lack of training on the convention.…”
Section: Discussionsupporting
confidence: 81%
“…For the development of the SD, the selection of bipolar adjectives was made from the adjective listings proposed by Osgood (1952). We also added adjectives from the Scale for the Assessment of Attitudes Toward Persons with Disabilities (Polo Sánchez, Fernández Jiménez, & Díaz Batanero, 2011;Verdugo, Arias, & Jenaro, 1994). From a list of 16 bipolar adjectives (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…A recent Latin American study examined attitudes toward PWD among 736 people in Chiapas, Mexico; authors reported several variables associated with positive attitudes, including having a family member with a disability, having a higher level of education, being younger, being single or married, living in an urban environment, and not practicing a religion (García Lara & Ortiz, 2011). Two studies conducted in Spain examined the attitudes of university students toward PWD and reported that the students generally had positive attitudes toward PWD (Moreno, Rodríguez, Saldaña, & Aguilera, 2006; Polo Sánchez, Jiménez, & Batanero, 2011). However, an extensive search in Colombian literature did not find any published studies about attitudes toward PWD.…”
Section: Introductionmentioning
confidence: 99%